2012
DOI: 10.1093/carcin/bgs232
|View full text |Cite
|
Sign up to set email alerts
|

The rebel angel: mutant p53 as the driving oncogene in breast cancer

Abstract: Breast cancer is the most frequent invasive tumor diagnosed in women, causing over 400 000 deaths yearly worldwide. Like other tumors, it is a disease with a complex, heterogeneous genetic and biochemical background. No single genomic or metabolic condition can be regarded as decisive for its formation and progression. However, a few key players can be pointed out and among them is the TP53 tumor suppressor gene, commonly mutated in breast cancer. In particular, TP53 mutations are exceptionally frequent and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
235
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(260 citation statements)
references
References 161 publications
(201 reference statements)
10
235
3
4
Order By: Relevance
“…In agreement, p53 Ser392 seems to be not phosphorylated in mutant p53 that is expressed in breast cancer (47), and most likely the loss of phosphorylation mark at this residue is responsible for maintenance of p53 oncogenic properties (reviewed in; ref. 47). Thus, phosphorylation of p53 at Ser392 may be important not only to stimulate p53-dependent transcription, but also could potentially decrease oncogenic properties of mutant p53.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In agreement, p53 Ser392 seems to be not phosphorylated in mutant p53 that is expressed in breast cancer (47), and most likely the loss of phosphorylation mark at this residue is responsible for maintenance of p53 oncogenic properties (reviewed in; ref. 47). Thus, phosphorylation of p53 at Ser392 may be important not only to stimulate p53-dependent transcription, but also could potentially decrease oncogenic properties of mutant p53.…”
Section: Discussionmentioning
confidence: 72%
“…Mutation of Ser392 to Ala, but not to phosphomimetic Asp, increased chemoresistance of some cancer cells and increased colony formation in soft agar, an indication of aggressive growth and greater oncogenic properties of p53 (46). In agreement, p53 Ser392 seems to be not phosphorylated in mutant p53 that is expressed in breast cancer (47), and most likely the loss of phosphorylation mark at this residue is responsible for maintenance of p53 oncogenic properties (reviewed in; ref. 47).…”
Section: Discussionmentioning
confidence: 82%
“…A large number of researches show that human peripheral blood lymphocytes hypoxantine-guanine phpsphoribosyl transferase (HPRT) gene, which is a chemical and ionizing radiation sensitive mutagen loci (Nicklas et al, 1991;Zimmer et al, 1997;Hamdan et al, 1999;Helleday et al, 2000), was closely related to the p53 and bcl-2 gene (Liu et al, 1997;Phillips, Gebow et al, 1997), which had been demonstrated strongly association with cancer development (Murray et al, 2012;Zeestraten et al, 2013),especially with breast cancer and esophageal cancer (Bellini et al, 2012;Walerych et al, 2012). Therefore, it is worthy to emphasize that the occupational X-ray radiation exposure might interact with phosphoribosyl gene mutation contribute to cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The P53 is central to δ-T3-mediated apoptosis in K562 cells as it regulates genes such as BCL2L1 (Lee et al, 2008), CASP8 (Liu et al, 2011), FAS (Muller et al, 1998), GADD45A (Xiao et al, 2000), MCL1 (Pietrzak and PuzianowskaKuznicka, 2008) and TNFRSF10B (Surget et al, 2012), all of which were over-expressed in the K562 cells following treatment with δ-T3. Mutations in the TP53 gene are reported to predispose an individual to various cancers such as breast cancer (Walerych et al, 2012), soft tissue sarcoma (Cordon-Cardo et al, 1994), bone (Kleihues et al, 1997) and brain (Sidransky et al, 1992) cancers, leukaemia (Felix et al, 1992) and the Li-Fraumeni Syndrome (Malkin et al, 1990). Yonish-Rouach et al (1991) had reported that restoring TP53 functions in tumour cells can reverse the susceptibility to cancer as the re-introduction of wild type TP53 gene into leukemic cells lacking this gene induced apoptotic cell death (Yonish-Rouach et al, 1991).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%